2011
DOI: 10.2118/137634-pa
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of the Impact of Injection-Water Salinity and Ionic Content on Oil Recovery From Carbonate Reservoirs

Abstract: SummaryThe impact of brine salinity and ion composition on oil recovery has been an area of research in recent years. Evidence from laboratory studies, supported by some field tests targeting mainly sandstones, has distinctly shown that injecting low-salinity water has a significant impact on oil recovery. Although the potential for carbonates has not been thoroughly investigated, some reported studies have excluded carbonates from this effect. The main objective of this paper is to investigate the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
348
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 505 publications
(370 citation statements)
references
References 16 publications
14
348
2
Order By: Relevance
“…Wettability alteration as an effect of LSF in carbonate rock is proven by Yousef et al (2011). Yousef et al (2011 conducted different laboratory studies to investigate the potential of LSF in carbonates.…”
Section: Wettability Alteration During Lsf In Carbonatementioning
confidence: 95%
See 4 more Smart Citations
“…Wettability alteration as an effect of LSF in carbonate rock is proven by Yousef et al (2011). Yousef et al (2011 conducted different laboratory studies to investigate the potential of LSF in carbonates.…”
Section: Wettability Alteration During Lsf In Carbonatementioning
confidence: 95%
“…From these observations Yousef et al (2011) concluded that the LSF in carbonate rock has a bigger impact on rock/fluid interactions (contact angle) than on fluid/fluid interaction (IFT). Yousef et al (2011).…”
Section: Wettability Alteration During Lsf In Carbonatementioning
confidence: 99%
See 3 more Smart Citations